Progress in Nano-Electro-Optics VI Nano-Optical Probing, Manipulation, Analysis, and Their Theoretical Bases - Ohtsu, Motoichi (Springer Series in Optical Sciences,, 2008)
This volume focuses on nano-optical probing, manipulation, and analysis. It begins with recent developments in near-field optical spectroscopy that clarify quantum states at the nanoscale, followed by a theory for a photon-electron-phonon interacting system at the nanoscale. Further topics include: visible laser desorption/ionization mass spectroscopy exhibiting near-field effects; a practical nanofabrication method with optical near fields applied to a SHG device; a theory and experimental achievements on optical transport of nanoparticles, selectively manipulated by resonant radiation force. Taken as a whole, this overview will be a valuable resource for engineers and scientists working in the field of nano-electro-optics.